PERAN KETERAMPILAN DAN PENGALAMAN USAHA TERHADAP KEBERHASILAN USAHA PARA PELAKU USAHA MAKANAN DI KECAMATAN TUAH MADANI KOTA PEKANBARU - Sukriani, Nurul; Dewi, Diana Sri; Febrina, Dian (Komunitas Manajemen Kompetitif, 2024)
This research aims to determine the Business Success of food entrepreneurs in Tuah Madani District, Pekanbaru, using the variables Business Experience and Entrepreneurial Skills to analyze their influence on Business Success. The population in this research is all food business actors who run food businesses in Tuah Madani District, Pekanbaru City, the exact number of which is not yet known. For an unknown population, the sample size in this study used the Wibisono formula and a sample of 97 people. Data collection was carried out using a questionnaire method, namely by providing a list of statements to respondents. The data analysis technique used is multiple linear regression analysis operated through the SPSS 20 for Windows program. The results of the research show that simultaneously and partially the variables Business Experience and Entrepreneurial Skills have a significant effect on Entrepreneurial Success among food business actors in Tuah Madani District, Pekanbaru. Keywords: Business Success, Business Experience, Entrepreneurial Skills